Simulation of Temperature Stratification in Atriums: Validation of Basic Model Features - Bajracharya, Susan (Journal of the Institute of Engineering, 2014)
Data on climate conditions, internal temperature conditions and building features were used to deter mine the relative effect of building features on heat gains and losses in a naturally ventilated atrium located at Groningen, Netherlands. Temperature estimates obtained by simulation were compared with measured data. It was found that food estimates of thermal stratification could be obtained by dividing the atrium into horizontal subzones. Mass flow modeling and time steps of less than one hour were found to be important features. DOI: http://dx.doi.org/10.3126/jie.v10i1.10897 Journal of the Institute of Engineering, Vol. 10, No. 1, 2014, pp. 157–171